Analisis Perilaku Konsumen dalam Keputusan Pembelian Sayuran Melalui Pendekatan Theory of Planned Behavior (Studi Kasus di Pasar Modern Cirtaland, Surabaya) - Maulana Zakaria Reyhan Pramana; Sri Tjondro Winarno; Indra Tjahaja Amir (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research was carried out, of course, had several objectives. The objectives of this research are; To analyze the effect of attitudes on consumers' purchase intentions for vegetables in CitraLand Modern Market, to analyze the effect of subjective norms on consumers' purchase intentions for vegetables at CitraLand Modern Markets, to analyze the effect of perceived behavioral control on consumers' purchase intentions of vegetables in CitraLand Modern Markets. , and to determine the effect of consumer buying intentions on purchasing decisions for vegetables at CitraLand Modern Market. The data analysis used in this research is descriptive analysis, SEM-PLS analysis. Testing the hypothesis in this study using the T test. The results of this study indicate that the attitude variable which has 3 indicators (purchase experience, purchase convenience and purchase pleasure) has a positive and significant effect on consumers' purchase intention variables on vegetable products at CitraLand Freshmarket. The subjective norm variable which also has 3 indicators (family support, close friend support, and the support of other important relatives) has a positive and significant effect on consumers' purchase intentions on vegetable products at CitraLand Freshmarket. The behavioral control perception variable which also has 3 indicators (ability to buy, has resources, and has time) has a positive and significant effect on consumer buying intentions on vegetable products at CitraLand Freshmarket. The purchase intention variable which also has 3 indicators (continue to make purchases, make purchases in a planned manner, and have the opportunity to make purchases) has a positive and significant effect on the variables of consumer purchasing decisions on vegetable products at CitraLand Freshmarket.